BMP-9 induced endothelial cell tubule formation and inhibition of migration involves Smad1 driven endothelin-1 production. - John E S Park; Dongmin Shao; Paul D Upton; Patricia Desouza; Ian M Adcock; Rachel J Davies; Nicholas W Morrell; Mark J D Griffiths; Stephen J Wort (PLoS ONE)
Background Bone morphogenetic proteins (BMPs) and their receptors, such as bone morphogenetic protein receptor (BMPR) II, have been implicated in a wide variety of disorders including pulmonary arterial hypertension (PAH). Similarly, endothelin-1 (ET-1), a mitogen and vasoconstrictor, is upregulated in PAH and endothelin receptor antagonists are used in its treatment. We sought to determine whether there is crosstalk between BMP signalling and the ET-1 axis in human pulmonary artery endothelial cells (HPAECs), possible mechanisms involved in such crosstalk and functional consequences thereof. Methodology/principal finding Using western blot, real time RT-PCR, ELISA and small RNA interference methods we provide evidence that in HPAECs BMP-9, but not BMP-2, -4 and -6 significantly stimulated ET-1 release under physiological concentrations. This release is mediated by both Smad1 and p38 MAPK and is independent of the canonical Smad4 pathway. Moreover, knocking down the ALK1 receptor or BMPR II attenuates BMP-9 stimulated ET-1 release, whilst causing a significant increase in prepro ET-1 mRNA transcription and mature peptide release. Finally, BMP-9 induced ET-1 release is involved in both inhibition of endothelial cell migration and promotion of tubule formation. Conclusions/significance Although our data does not support an important role for BMP-9 as a source of increased endothelial ET-1 production seen in human PAH, BMP-9 stimulated ET-1 production is likely to be important in angiogenesis and vascular stability. However, increased ET-1 production by endothelial cells as a consequence of BMPR II dysfunction may be clinically relevant in the pathogenesis of PAH.